Integrating Sustainability Issues into Investment Decision Evaluation - Efimova, Olga V. (Journal of Reviews on Global Economics, 2018)
The paper investigates the issues of integrating ESG factors into investment decision-making process. Based on the available investor surveys, academic research, the analysis of the Russian companies` non-financial reports, Bloomberg ESG data, Corporate Sustainability and Responsibility indexes and their sectoral aspects, as well as Russian ecological-stock index ERAX and stock exchange index MICEX dynamics the paper concluded that ESG factors have a material impact on corporate financial performance. At the same time there are barriers to the full ESG integration in the investment process primarily connected with the lack of standardized data, information comparability, reliability, completeness and timeliness; limited knowledge and guidance for ESG risk and opportunity measures and appropriate analytical tools as well as lack of dialogue between the investment community and the reporting companies. To contribute to the problem development this paper presents an approach of integrating ESG factors at different stages of investment analysis and business valuation.